Synthesis of Binary Bi2S3/ZnO Nanorod Array Heterostructure and Their Photoelectrochemical Performance. (8th August 2019) - AL-Zahrani, Asla A.; Zainal, Zulkarnain; Talib, Zainal Abidin; Lim, Hong Ngee; Mohd Fudzi, Laimy; Holi, Araa Mebdir; Sarif @ Mohd Ali, Mahanim
Abstract : One of the most effective strategies to improve the photoconversion efficiency in the photoelectrochemical cell is by using an assembly of heterostructures. To do so, a simple and inexpensive method, that is successive ionic layer adsorption and reaction (SILAR), is used to deposit the narrow band gap energy semiconductor Bi2 S3 on ZnO nanorod arrays (NRAs) at different SILAR cycles. The obtained binary heterostructure thin films were characterized by using X-ray diffraction (XRD), UV-Vis Spectroscopy, field emission scanning electron microscopy (FE-SEM), energy dispersive X-ray analysis (EDX), Raman spectroscopy, high-resolution transmission electron microscopy (HRTEM), and linear sweep voltammogram (LSV) to prove the crystal structure, optical properties, band gap energy, morphological structure, composition of elements, and electrical properties. The XRD revealed that ZnO NRAs possessed a single wurtzite crystal structure while Bi2 S3 possessed an orthorhombic crystal structure. The as-fabricated Bi2 S3 /ZnO heterostructure exhibited enhanced visible light absorption and charge separation efficiency of photoinduced electron-hole pairs. The band gap energy of binary heterostructure Bi2 S3 /ZnO NRAs is 3.11, 3.00, 2.33, 1.96, and 1.89 eV at 3, 5, 7, 9, and 11 SILAR cycles, respectively, confirming the substantial improvement of ZnO NRA optical properties. The highest photocurrent density has been achieved by 1.92 mA/cm 2 of Bi2 S3 /ZnO NRAs fabricated at 7 cycles, exhibiting sixfold enhancement compared to that of intrinsic ZnO NRAs (0.336 mA/cm 2 ). This impressive enhancement was ascribed to the significant improvement in morphological structure, crystallinity, and optical properties of heterostructure photoanodes. Significant improvement was achieved in the photoelectrochemical cell (PEC) performance attributed to the fast separation, low recombination rate, and low impedance of the photoinduced electron-hole pairs as shown throughout the electrochemical impedance spectra.